Antimicrobial Potential of Strontium Hydroxide on Bacteria Associated with Peri-Implantitis - Hatem Alshammari; Jessica Neilands; Gunnel Svensäter; Andreas Stavropoulos (MDPI AG, 2021)
Background: Peri-implantitis due to infection of dental implants is a common complication that may cause significant patient morbidity. In this study, we investigated the antimicrobial potential of Sr(OH)2 against different bacteria associated with peri-implantitis. Methods: The antimicrobial potential of five concentrations of Sr(OH)2 (100, 10, 1, 0.1, and 0.01 mM) was assessed with agar diffusion test, minimal inhibitory concentration (MIC), and biofilm viability assays against six bacteria commonly associated with biomaterial infections: Streptococcus mitis, Staphylococcus epidermidis, Aggregatibacter actinomycetemcomitans, Porphyromonas gingivalis, Escherichia coli, and Fusobacterium nucleatum. Results: Zones of inhibition were only observed for, 0.01, 0.1, and 1 mM of Sr(OH)2 tested against P. gingivalis, in the agar diffusion test. Growth inhibition in planktonic cultures was achieved at 10 mM for all species tested (p < 0.001). In biofilm viability assay, 10 and 100 mM Sr(OH)2 showed potent bactericidal affect against S. mitis, S. epidermidis, A. actinomycetemcomitans, E. coli, and P. gingivalis. Conclusions: The findings of this study indicate that Sr(OH)2 has antimicrobial properties against bacteria associated with peri-implantitis.